1979
DOI: 10.1111/j.1600-0722.1979.tb00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic study of distribution patterns of metals which occur as corrosion products from dental restorations

Abstract: – Radioactive chromium, cobalt, gold and mercury, all of which may occur as corrosion products from dental restorations, were injected in single doses via the tail vein of mice and an in vivo analysis of their distribution was performed using whole‐body autoradiography. Gold seemed to be inert and went mainly to the liver and bones. The other elements studied were distributed widely in the body and remained for a long period of time in specific target organs and tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…The novel finding of this study was that we obtained unequivocal evidence that there were larger deposits of cobalt locally in the mineralized bone tissue surrounding joint implants than elsewhere in the skeleton. Other authors performed animal experiments and reported similar findings 37–39. However, a separate demonstration of the mineralized and nonmineralized bone tissue was not conducted in these studies.…”
Section: Discussionmentioning
confidence: 68%
“…The novel finding of this study was that we obtained unequivocal evidence that there were larger deposits of cobalt locally in the mineralized bone tissue surrounding joint implants than elsewhere in the skeleton. Other authors performed animal experiments and reported similar findings 37–39. However, a separate demonstration of the mineralized and nonmineralized bone tissue was not conducted in these studies.…”
Section: Discussionmentioning
confidence: 68%
“…Clinically, subjective discomfort has also been reported (7,8). It has been proposed that different compounds released from dental restorations into the saliva can reach adjacent target tissues or interfere with different biochemical reactions in the body via the blood and the lymphatic systems (9,10). Recently,BRUNE et al (11) demonstrated in rats that different compounds of various amalgams could be transferred to the blood system after gastrointestinal administration and accumulate in kidney, liver and lung tissues.…”
mentioning
confidence: 99%
“…Recently,BRUNE et al (11) demonstrated in rats that different compounds of various amalgams could be transferred to the blood system after gastrointestinal administration and accumulate in kidney, liver and lung tissues. The risk for accumtilation of products from dental restorative materials has been discussed in detail elsewhere (9).…”
mentioning
confidence: 99%
“…The distribution of elements released from dental alloys into the environmental tissues, target organs and surrounding fluids and air has been investigated (e.g. [9][10][11][12][13][14][15][16][17][18][19][20][21]. Among the different release mechanisms, various corrosion processes have received a great deal of attention.…”
mentioning
confidence: 99%